CASE STUDY MENURUNKAN TINGKAT STRES KERJA PERAWAT DENGAN PENERAPAN TERAPI SELF HEALING MELALUI TEKNIK AFIRMASI PADA PERAWAT ADVANCE DI PK3D JAKARTA - Dina Krismayanti (2023)
Work stress is a condition which humans are in a mismatch between skills and abilities with job demands, resulting in obstacles at the workplace. Nurses as a health workers are at high risk of being exposed to work stress. Seeing the conditions in the hospital and pre-hospital, nurses are always at the forefront in providing maximum nursing care to maximize patient health. The results of interviews and observations conducted by the author at PK3D (Pusat Krisis dan Kegawatdaruratan Daerah) Jakarta showed that out of 10 nurses, 1 nurse (20%) had high stress levels, 4 nurses (40%) had moderate stress levels and 4 nurses (40 %) have a low level of stress / do not experience work stress. Based on these results, the authors conducted evidence-based nursing in the form of applying self-healing using affirmation techniques. The intervention lasts for 4 days in 2 weeks by conducting question and answer or pre-test and post-test to nurses. The evaluation results showed that of the 6 nurses who experienced moderate to high work stress after the application of affirmation techniques, 1 nurse (17%) had moderate stress levels and 5 nurses (83%) had low stress levels/did not experience work stress. This shows that the affirmation technique is proven to help reduce work stress levels in nurses.